Assessment of coastal erosion structures along Pahang and Johor coastlines - Salin, U. N; Ramli, Muhammad Zahir; Hikmatullah Sahib, Siti Ayishah Thaminah; Ibrahim, N.A.N (2022)
Morphological evolution of a coast occurs naturally and could be exacerbated by anthropogenic activities. In a natural setting, the evolution would be able to recover by itself with time but due to the influence of human activities, these recoveries tend to not occur. Furthermore, the issue of sea level rise that has been continuously highlighted is an example of the said natural factors that has been exacerbated by human activities. The potential increase in sea level rise may cause detrimental effects such as worsening conditions of monsoon seasons and the occurrence of wave overtopping on coastal areas. Over the past few years, the effects of monsoon towards the Malaysian coastal area that has caused damage to properties, roads, and other infrastructures. This study highlights the changes that occur to the selected coasts of Pahang and Johor during the different monsoon seasons of 2021 and 2022. Sampling sites are chosen due to the presence of coastal structures such as revetment, groynes, seawall, and geobag which were identified via satellite imagery and site observation. The results signify that during the Northeast monsoon, most of the coasts experience erosion with the greatest change to be found at Hulu Tering, Pahang and Tanjung Kempit, Johor.